Interactions between plant roots and the structure of compacted soils - Burr-Hersey, Jasmine Emma (2020)
Compaction is a form of soil physical degradation. It occurs through both human-induced and natural mechanisms such as the passage of heavy farm machinery in agricultural settings as well as the impact of animal trampling and glaciation in natural ecosystems. It results in the rearrangement of soil particles, resulting in an increase in bulk density and subsequent loss of porosity and pore connectivity. These changes in the soil matrix make it difficult for plant roots to penetrate deep into the soil profile as the connected macropore network which provides the path of least resistance has been destroyed. Currently, there are limited ways to remediate the impact of soil compaction, mechanical methods that exist only provide temporary relief and often exacerbate the problem at depth. The use of plant roots as a 'biotillage' tool could offer a natural means to help remediate soils subject to compaction. The objective of this study was to visualise and quantify the root architectures of selected cover crop and wild plant species grown in a variety of compacted soil conditions. To do this three-dimensional visualisations of the root architecture were generated via X-ray Computed Tomography, using a number of different automated and semi-automated root-segmentation techniques. The impact of plant root growth on soil structure was then analysed at both rhizosphere and soil column scales, over timescales of several weeks. In high soil compaction treatments changes in pore space were localised to the rhizosphere zone up to 420 µm distance from the root surface. Across the species investigated the porosity was always greatest closest to the root surface and decreased with distance form the roots surface. This trend was also observed when plants were grown in different soil textures. Soil texture was observed to significantly affect plant growth, with notably less root and shoot development by plants grown in the clay soils in comparison to the clay loam and sand treatments. The generation of root mass was species-dependent and linked to the penetration resistance of the soil. These parameters subsequently affected average root diameters of the plants, which had a direct effect on pore space creation in the rhizosphere. Roots with different morphological traits were observed to respond contrastingly to a compacted soil layer, with taprooted species undergoing greatest architectural change in comparison to fibrous root systems. The work indicates that changes to soil structure via the growth of plant roots occurs primarily in root:soil contact zone, and is a temporally dynamic process. Tap-rooted plants appear to be particularly effective in terms of being able to grow in highly compacted soils. These findings have implications for the potential remediation of compacted soils, as they indicate that plants demonstrate an inherent ability to instigate soil structural genesis, but this differs between species.